An evaluation of the performance of hot mix asphalt containing calcium carbide residue as a filler. (20th November 2020) - Dulaimi, Anmar; Shanbara, Hayder Kamil; Jafer, Hassnen; Sadique, Monower
Highlights: The feasibility of using carbide lime as an alternative filler in hot mix asphalt was examined. The use of CCR improved the stiffness of hot mix asphalt mixtures. Improving crack initiation and propagation resistance have been achieved with the CCR. The CCR filler enhanced the rutting performance of hot mix asphalt mixtures. Abstract: The reduction of both environmental problems and construction costs has motivated the asphalt pavement industry to increasingly use waste materials as alternative raw materials in road pavements construction. This investigation aims to explore the potential of waste calcium carbide residue (CCR) for use as a filler in hot mix asphalt (HMA), by substituting traditional limestone filler in various proportions. Asphalt mixes were prepared using different CCR ratios (0%, 3% and 6%) by aggregate dry weight, their strength, properties and performance evaluated against the indirect tensile stiffness modulus, rutting, crack initiation, crack propagation and moisture damage. The results show that stiffness modulus and resistance to permanent deformation and cracks have been enhanced due to the addition of CCR. HMA modified with CCR was also found to be less sensitive to water damage than traditional HMA with limestone filler. A toxicity characteristic leaching procedure (TCLP) test revealed that the CCR used in the production of HMA has no environmental impact. Therefore, based on this study, CCR can be considered as a plausible alternative to conventional filler in HMA, the implication being that large amounts of waste carbide lime can be removed from landfill, thereby significantly reducing environmental damage.